2018
DOI: 10.1177/2397198318809224
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the clinical phenotype of systemic sclerosis patients in Iran and France in two university centers

Abstract: Objectives: Systemic sclerosis is a severe and rare chronic auto-immune multisystem disorder characterized by vasculopathy and skin stiffness. Ethnic and geographical origin can influence the outcomes. In this study, we compared the phenotypic characteristics of Iranian and French patients. Methods: This cross-sectional study was performed on 200 Iranian and 268 French systemic sclerosis patients. Iranian patients collected from the Iranian systemic sclerosis cohort of the Rheumatology Research Center, Shariat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 43 publications
1
4
0
Order By: Relevance
“…As this marker significantly correlates with disease severity (diffuse form) and pulmonary involvement, this finding could suggest the potential of miR-27a for differentiating patients from healthy ones as well as utilizing it in the assessment of disease progression, although this hypothesis needs further robust examinations in much larger populations of the SSc patients to draw a comprehensive conclusion. Also, the expression of miR-27a was evaluated in subsets of patients positive for ACA and ribonucleoprotein autoantibodies; it was found that the downregulation of miR-27a is associated with negative ACA, which can be explained by the very low frequency of ACA in Iranian SSc patients, also ACA is more prevalent among the limited subtype of the SSc and this is consistent with our data 35 37 . Besides, it was shown that the downregulation of miR-27a which is found in diffuse patients is also associated with positive anti-ribonucleoprotein antibodies.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…As this marker significantly correlates with disease severity (diffuse form) and pulmonary involvement, this finding could suggest the potential of miR-27a for differentiating patients from healthy ones as well as utilizing it in the assessment of disease progression, although this hypothesis needs further robust examinations in much larger populations of the SSc patients to draw a comprehensive conclusion. Also, the expression of miR-27a was evaluated in subsets of patients positive for ACA and ribonucleoprotein autoantibodies; it was found that the downregulation of miR-27a is associated with negative ACA, which can be explained by the very low frequency of ACA in Iranian SSc patients, also ACA is more prevalent among the limited subtype of the SSc and this is consistent with our data 35 37 . Besides, it was shown that the downregulation of miR-27a which is found in diffuse patients is also associated with positive anti-ribonucleoprotein antibodies.…”
Section: Discussionsupporting
confidence: 88%
“…In this regard, Deng K, et al have shown the negative regulation of PPARγ by miR-27a, too 50 . Besides, in a study conducted by Ji-Hoon Cho, et al with a systems biology approach, it was found that miR-27a along with miR-23a and miR24 is upregulated in response to TGF-β by the Zeb-1 transcription factor which is a major participant in EMT 35 . It could be suggested that miR-27a elevation in these instances may take place upon over-activation of the TGF-β signaling pathway as a negative feedback mechanism to attenuate its physiological consequences.…”
Section: Discussionmentioning
confidence: 99%
“…Studies directly comparing patients from different countries have also underscored the variable severity of SSc among patients depending on their geographical origin. For example, review of the EUSTAR database revealed that Iranian patients with SSc more frequently had dcSSc and a lower FVC value than French patients [27]. Similarly, American patients had more severe phenotypes, with a higher prevalence of dcSSc than French patients [8].…”
Section: Discussionmentioning
confidence: 99%
“…11,15 Geographical differences in the clinical phenotype and the autoantibody profile have been well described, further highlighting the diversity of this complex disease. 16,17 There is sparse data from the Indian subcontinent in this respect. [18][19][20] We report an exploratory cluster analysis utilizing all relevant clinical parameters and the autoantibody profile from the baseline data of the prospective SSc registry in India.…”
Section: Introductionmentioning
confidence: 99%